Report to participating governments on the I.L.O. Asian regional seminar on vocational rehabilitation held in Manila, Philippines from 7-23 November 1970 (I.L.O., 1961)
International Labour Office. Expanded programme of technical assistance. ILO/TAP/AFE/R. 11. Stencil.